Examining Relationships of Destination Image, Service Quality, e-WOM, and Revisit Intention to Sabang Island, Indonesia - Rangga Restu Prayogo; Arinta Kusumawardhani (Department of Management, Faculty of Economics and Business, Brawijaya University, 2016)
The purpose of this research is to study the relationship among destination image, service quality, e-WOM, and revisit intentions in the tourism industry. A questionnaire given to tourists who visit one of the farrest island in western part of Indonesia, Sabang Island and using sampling through the convenience sampling. A structural equation model (SEM) test with WarpPLS 3.0 was used to test the relationship between research variables. This research gathered from 150 respondents. The empirical results from PLS-SEM showed that; the destination image positive affect e-WOM and revisit intention; service quality affect e-WOM and revisit intention; e-WOM positive affect to revisit intention tourists. The implications and future research issues were discussed.